One world or two? Science–policy interactions in the climate field. Issue 4 (2nd October 2018) - Sundqvist, Göran; Gasper, Des; St.Clair, Asunción Lera; Hermansen, Erlend A.T.; Yearley, Steven; Øvstebø Tvedten, Irene; Wynne, Brian
ABSTRACT: This article assesses how science–policy interactions are conceptualized in the social sciences with special reference to climate change and the IPCC. In terms of the dimension of distance (or proximity) between science and policy, we discern two ideal-type cases: a 'two-worlds' and a 'one-world' perspective. The first understands science and policy as independent spheres separated by a clear gap, while the second perceives science and policy as tightly coupled. These two perspectives, presented here in detail and in various sub-variants in order to show their complexity, appear dominant also in the discussions on how to improve, not only describe, the interaction between science and policy. We argue that this situation of opposing perspectives is not beneficial, nor properly recognized by scholars in the field. In response to this, we present a typology that may serve as a modest and judicious way for thinking about and making more nuanced choices in designing science–policy relations.